Identification of Misconceptions in Science Learning During the Covid-19 Pandemic Using the CRI (Certainty of Response Index) Method for Primary school Students - Elisa Prezilia Dewi; Fitria Wulandari (Jurnal Penelitian Pendidikan IPA, 2021)
This research aims to identify the science misconceptions of elementary school students using CRI (Certainty of Response Index), as well as to describe the factors of students' misconceptions at Primary school Muhammadiyah 8 Tulangan. This research uses the descriptive qualitative method. The subjects used in this study were class V, totaling 26 students. Data collection techniques using the test, interviews, and documentation. Based on the results obtained from the research as a whole, the highest misconception is about the concept of the effect of temperature on changes in the shape of objects by 44.70%, the concept of temperature and heat by 39.42%, and the lowest misconception is about the concept of object properties by 32.04%. From the results of research using the CRI (Certainty of Response Index) method, several factors cause misconceptions, namely from the students themselves who come from the initial concept and students wrong intuition, then misconceptions from the teacher, as well as incomplete book explanations. So it can be concluded that science learning during the covid-19 pandemic caused misconceptions for students of Primary school Muhammadiyah 8 Tulangan